Alternative transport fuels for the future. (12th May 2004) - MacLean, Heather L.; Lave, Lester B.; Griffin, W. Michael
Petroleum fuels, which are not sustainable and which contribute substantially to greenhouse gas emissions, power nearly all light-duty vehicles. We review the North American literature on alternative fuels such as natural gas, ethanol from corn and biomass, and hydrogen and electricity from renewable resources, as well as propulsion systems including internal combustion engines, electric motors, and fuel cells. Vehicle characteristics including emissions, safety and consumer attributes such as range and power are examined. Results for greenhouse gas emissions and energy use for the well-to-wheel (fuel production and vehicle operation) aspects of the life cycles of the fuel/vehicle combinations are evaluated. While fuel cells and batteries might some day be attractive, in the near term they cannot replace the internal combustion engine. We focus on ethanol and explore its potential to replace nearly all gasoline used in the United States and Canada. We conclude that ethanol produced from biomass is an attractive near/midterm fuel among those that are sustainable.